Efcacy of Low-Intensity Aerobic Exercise and Aerobic Combined with Resistance Exercise on Pain, Respiratory Function, Fatigue and Qualityof Life in Nursing Patients - Šarūnas Kvietkauskas; Vilma Juodžbalienė (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. In older people with multiple comorbidities, quality of life declines due to physical deterioration, which may also contribute to psychological deterioration (Nóbrega et al., 2009; Subramaniam et al., 2019). In such cases, it is important to ensure adequate physical activity, as it can improve their physical and psychological condition (Bricca et al., 2020). Physical activity including aerobic exercises, resistance exercises, and stretching exercises can improve the quality of life in elderly (López-Torres, 2019), but it remains unclear which physical exercises are more effective.